PERFORMANCE EFFICIENCY OF THE JORDANIAN ISLAMIC BANKS USING DATA ENVELOPMENT ANALYSIS AND FINANCIAL RATIOS ANALYSIS - Ajlouni, Moh'd M.; Omari, Hamed O. (European Scientific Journal, ESJ, 2013)
The purpose of this study is to investigate and compare the development of the relative efficiency of Jordanian Islamic banks performance over time (2005-2009), using two different approaches: Malmquist Data Envelopment Analysis and Financial Ratio Analysis. There are 3 Islamic banks in Jordan, one of which has been established recently, 2010. The results reveal that Jordanian Islamic banks are constantly efficient in term of their inputs producing actual outputs, using both approaches, during the study period. However, the variation between the sample banks is not significant. In addition, there is no significant evidence on the association between DEA and FRA bank rankings It is recommended that Jordanian Islamic banks managers should increase their banks efficiency by improving recourse utilization to produce optimal outputs.